PENGARUH TEKANAN DAN LAMA PENUGASAN TERHADAP INDEPENDENSI AUDITOR EKSTERNAL PEMERINTAH - Aizhar Ashari; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2017)
Many factors can affect the independence of auditor. This study aims to determine the effect of fidelity pressure, time pressure, and assignment range towards auditor independence of the Audit Board of the Republic of Indonesia. The study used primary data derived from respondents who are auditors on the Audit Board of Indonesia Representative of Provinsi Bali. This study used four variables. Three variables are fidelity pressure, time pressure, and assignment range, thence one dependent variable is auditor independence. The data were analyzed using multiple linear regression test. The results showed that fidelity pressure had negative effect on auditor independence, and time pressure had a possitive effect towards auditor independence. Meanwhile assignment range did not gave a significant effect to auditor independence.